Evaluation of a Dengue NS1 capture ELISA assay for the rapid detection of Dengue - Shamala Devi Sekaran, Ew Cheng Lan, Kanthesh Basalingappa Mahesawarappa, Ramapraba Appanna and Geetha Subramaniam (The Journal of Infection in Developing Countries, 2007)
Background: Early definitive diagnosis of dengue virus infections is essential for the timely management of dengue infections. In this study, we evaluated the PanBio Dengue NS1 Antigen Capture ELISA for the detection of dengue virus NS1 antigen in patients' sera.Methodology: A total of 206 serum samples and 8 viral isolates were used to evaluate the kits. These samples were analysed using TaqMan RT-PCR, an in-house IgM ELISA, a hemagglutination inhibition (HI) assay, and the PanBio NS1 ELISA.Results: Out of the 66 culture positive sera that tested positive using the TaqMan RT-PCR, NS1 antigen was detected in 91% with sensitivity being higher in primary acute sera than in secondary acute sera. The detection rate by PanBio Dengue NS1 Antigen Capture ELISA in the absence of IgM was 91.6% as compared to 48.3% in the presence of IgM. The overall sensitivity of the PanBio Dengue NS1 Antigen Capture ELISA in the detection of dengue in culture positive sera was 91.6%.Conclusions: The PanBio ELISA is a highly specific and sensitive assay for the detection of dengue NS1 antigen. The assay was able to detect NS1 antigen in convalescent sera up until day 10 of infection, whereas viral RNA was undetectable via PCR by day 7. However, as it is most effective during the acute phase of the disease, this kit should be used together with the IgM to increase the sensitivity of detection, especially in areas with higher prevalence of secondary dengue virus infections.